Abordagem baseada em Cenários para Extração de Requisitos de Interoperabilidade de Sistemas-de-Sistemas a partir de Processos-de-Processos de Negócio - Murilo Gustavo Nabarrete Costa (2024)
Context: From the conception of new organizational alliances that may occur through partnerships, mergers, or acquisitions, a challenge arises in integrating the business processes of their member organizations to achieve broader business goals that could not previously be realized. This integration results in the creation of new complex and dynamic business processes, known as Process-of-Business Processes (PoP). Typically, these processes are automated by distinct software systems, which during the integration process, they begin to interoperate to perform functionalities broader than those that could be executed by a single software system, resulting in the formation of Systems-of-Systems (SoS). Problem: The SoS domain presents new challenges for requirement extraction, especially interoperability requirements, due to the characteristics of these types of systems, such as managerial and operational independence, as well as their dynamic architecture. Interoperability requirements are crucial to ensuring adequate communication among the constituent systems composing the SoS. However, works found in the literature generally provide solutions for extracting interoperability requirements in more advanced phases of the SoS lifecycle, such as the architectural design phase. These works also tend to overlook business-level information as a source for requirement extraction, despite its essential role in ensuring a proper understanding of interoperability and alignment with the technical level. Objective: The main contribution of this master's thesis is to propose an approach based on scenarios in the BPMN (Business Process Model and Notation) notation for systematic extraction of interoperability requirements. Models representing PoP were used as information source. The approach includes a metamodel, containing classes to represent interoperability among the business processes of the PoP using BPMN elements, and a set of guidelines for systematic and automatic extraction of interoperability requirements based on classes from this metamodel. Research Method: The work was conducted using the Design Science Research method, resulting in the production of the following artifacts: six abstract scenarios, a variant of these abstract scenarios, a metamodel, and a set of guidelines for extracting SoS interoperability requirements. Result: An automated approach for extracting and specifying interoperability requirements during SoS Requirements Engineering. This approach uses PoP models that conform to the interoperability abstract scenarios defined in this work, aiming to mitigate existing challenges when handling the dynamism of interoperability among PoP processes and, consequently, among SoS constituents. Therefore, the approach ensures the alignment between business and technical levels, directly contributing to obtaining their strategic business goals.